Understanding the role of local authority's policies and I/NGOs in promoting sustainable livelihoods in Northwest Syria: The greater Idleb case - Sammak, Omar (Hasan Kalyoncu Üniversitesi Lisansüstü Eğitim Enstitüsü, 2024)
The interplay between local authorities and NGOs in conflict-affected areas and how they promote sustainable livelihoods is complex and varied. In Greater Idleb, NGOs drive the economic sector through service provision and capacity building, while local governance ensures sustainability and the integration of initiatives within public development frameworks. This study aimed to understand how these two actors can work together to achieve sustainable livelihoods while also exploring any other factors that can contribute to the promotion of the livelihoods of the community and ensure its sustainability. The study uses qualitative research and semi-structured interviews to gather diverse perspectives from community residents, local authorities, and humanitarian workers, adopting an exploratory approach in order to gain comprehensive insights into the study topic. While using the descriptive research approach, the case study gives unique insights into the dynamics of governance, sustainable livelihood practices, and coordination in a conflict-affected region. An intensive fieldwork phase of interviews with key stakeholders within the state and governance structures helped understand the state perspective on these initiatives and how they can be used as entry points for cooperation between NGOs and LAs. It emphasizes the importance of a well-designed legal framework, continuous evaluation of laws, and the need for local authorities to enhance their analytical, operational, and political capacities to foster economic growth, stability, and social cohesion. On the other hand, the study highlights the need for greater inclusivity and transparency in legislative processes, promoting education and learning to enable young people and workers to cope with labor market needs and improve labor skills. Specifically, there is an urgent need to strengthen community participation and balance the needs of society with development strategies and policies. To enhance the role of local authorities in fostering sustainable livelihoods, it is essential to adopt inclusive governance structures and transparent mechanisms that facilitate community participation and decision-making. Strengthening coordination mechanisms, promoting transparency, and building on successful experiences are crucial steps in ensuring that local authorities are able to effectively support sustainable livelihoods for the community. In conclusion, the analysis highlights the significance of establishing efficient collaborations among NGOs, local authorities, and various stakeholders to achieve sustainable livelihoods and enhance living conditions in Greater Idlib. The analysis highlights that local authorities are not capable of easing the livelihood of the residents without the involvement of INGOs and the community. Without the involvement of NGOs and the community, these goals may remain out of reach

Çatışmalardan etkilenen bölgelerde yerel otoriteler ile STK'lar arasındaki etkileşim ve sürdürülebilir geçim kaynaklarını teşvik etmesi karmaşık ve çeşitlidir. İdlib'de, STK'lar hizmet sağlama ve kapasite oluşturma yoluyla ekonomik sektörü yönlendirirken, yerel yönetim sürdürülebilirliği ve girişimlerin kamu kalkınmasına entegrasyonunu sağlamaktadır. Bu çalışma, bu iki aktörün sürdürülebilir geçim kaynaklarını başarılı bir şekilde nasıl elde edebileceğini anlamayı amaçlamıştır, aynı zamanda topluluğun geçim kaynaklarının teşvikine ve sürdürülebilirliğine katkıda bulunabilecek diğer faktörleri de araştırmaktadır. Çalışma, kapsamlı öngörüler elde etmek için irdeleyeci bir yaklaşım benimseyerek topluluk üyeleri, yerel otoriteler ve insani yardım çalışanlarından farklı bakış açıları toplamaya yönelik nitel araştırma ve yarı yapılandırılmış görüşmeleri kullanmıştır. Tanımlayıcı araştırma yaklaşımını kullanırken, durum çalışması çatışmadan etkilenen bir bölgede yönetişim dinamikleri, sürdürülebilir geçim uygulamaları ve koordinasyonu hakkında öngörüler sunmaktadır. Devlet ve yönetişim yapıları içindeki ana paydaşlarla yapılan yoğun saha çalışması ve görüşmeler, bu girişimler hakkındaki devlet perspektifini anlamaya ve STK'lar ile yerel otoriteler arasındaki iş birliği için nasıl kullanılabileceğini anlamaya yardımcı olmaktadır. Çalışma aynı zamanda, iyi tasarlanmış bir yasal çerçevenin, yasaların sürekli değerlendirilmesinin ve yerel otoritelerin ekonomik büyüme, istikrar ve sosyal uyumu teşvik etmek için analitik, operasyonel ve siyasi kapasitelerini artırma ihtiyacının önemine eğilmektedir. Öte yandan, çalışma yasama süreçlerinde daha fazla katılımcılık ve şeffaflığın gerekliliğini vurgulamakta, gençlerin ve işçilerin işgücü piyasası ihtiyaçlarıyla başa çıkabilmeleri ve iş becerilerini geliştirmeleri için eğitimin ve öğrenmenin teşvik edilmesini savunmaktadır. Özellikle, toplum katılımını güçlendirmenin ve toplumun ihtiyaçlarını karşılama stratejileriyle ve politikalarıyla dengelemenin acil bir ihtiyaç olduğunu ileri sürmektedir. Sürdürülebilir geçim kaynaklarını teşvik etmede yerel otoritelerin rolünü geliştirmek için, toplum katılımını ve karar verme süreçlerini kolaylaştıran kapsayıcı yönetişim yapıları ve şeffaf mekanizmaların benimsenmesi büyük öneme sahiptir. Koordinasyon mekanizmalarının güçlendirilmesi, şeffaflığın teşvik edilmesi ve başarılı deneyimlere dayanması, yerel otoritelerin toplum için sürdürülebilir geçim kaynaklarını etkili bir şekilde destekleyebilmelerini sağlamak için önemli adımlardır. Sonuç olarak, analiz İdlib'de sürdürülebilir geçim kaynaklarını elde etmek ve yaşam koşullarını iyileştirmek için STK'lar, yerel otoriteler ve çeşitli paydaşlar arasında etkin iş birliklerinin kurulmasının önemini vurgulamaktadır. Analiz yerel otoritelerin, uluslararası STK'ları ve toplumun katılımı olmadan, bölge sakinlerinin geçim kaynaklarını rahatlatamayacağını belirtmektedir. STK'ları ve toplumun katılımı olmadan, bu hedeflere ulaşılamayabilecektir.
Keywords: Sustainable Livelihood; Local Authority; Policy; Coordination; Community Engagement